The role of virtual endoscopy in surgical practice of otolaryngology head and neck surgery: a review article - Jafar, Ali; Alali, Bader (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Virtual endoscopy involves the acquisition of data to generate a three-dimensional view of hollow anatomical structures. This interface would allow for the realistic integration of anatomical structures in complex cavities involving sinuses, larynx, and ears. Current literature lacks updated review on the role virtual endoscopy in otolaryngological practice. This paper serves to highlight the use of virtual endoscopy in amongst three main domains: otology, rhinology and laryngology. Review of literature were conducted using various databases including, Pubmed, Scopus, Embase, Web of Science, google scholar. Only papers in full text, English language, and relevant to our objectives were included. A critical descriptive review of the papers were performed to illustrate the strength and weakness on the utilization of virtual endoscopy as a surgical planning tool in otorhinolaryngology practice. The advantages of applying VE in our practice serves two folds; as an educational tool for novice trainees mainly for surgical skill acquisition and as a pre-op planning to understand complex anatomical narrow operative fields. Our paper is the first to demonstrate the most updated commentary review article of the application of virtual endoscopy in sinus surgery, laryngeal airway evaluation and the assessment of ear surgery.